(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Physical training is an integral part of cadets’ training, which ensures the effectiveness of their future professional activities. Among the main physical qualities necessary for performing tasks in conditions of increased physical and psychological stress, coordination abilities occupy a special place. Exercises aimed at maintaining balance, speed of action and overcoming obstacles can significantly increase the ability of border guards to effectively respond to threatening situations. They play a crucial role in quick decision-making, accuracy of actions and effective use of physical potential. Modern theory and practice of pedagogical education and sports training refers coordination abilities to one of the least studied motor qualities. It is known that coordination training still remains a poorly developed section of the theory and methodology of physical education due to the multicomponent nature and complexity of this area. The article considers methods for developing coordination in cadets, and also analyzes their impact on the professional development of future border guards. The importance of developing coordination abilities in the process of physical training of cadets is studied. The role of coordination in increasing the efficiency of performing official tasks, in particular under conditions of high workload, is determined. Modern approaches and methods that contribute to improving coordination are described. The results of the study indicate a close connection between the level of coordination abilities of cadets and their readiness to perform professional duties. Attention is paid to the need to integrate specialized exercises into training programs to maximize the disclosure of physical potential. The recommendations given may be useful for developing new approaches to physical education in the system of professional training of border guards. At the same time, issues related to the definition of the most important coordination abilities in practical activities and the establishment of their share of significance in the overall structure require more detailed consideration.